Informed Intuition Model: Integrating Cognition in Formulating Strategic Problems Innovatively - Fatimah, Siti; Chadir, Mohammad (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This study aims to examine the role of informed intuition and combinatorial cognition models in innovative strategic problem formulation. In the context of strategic decision-making, the combination of analytical thinking and intuition plays an important role in overcoming uncertainty and generating innovative solutions. Based on the literature review, it was found that intuition based on experience and data can accelerate the decision-making process, especially in complex and uncertain situations. However, the integration of intuition and analysis requires a balance so that the resulting decisions are effective and appropriate. This study provides important insights into how both elements can function synergistically in improving the quality of strategic decisions